2017
DOI: 10.9790/9622-0702025254
|View full text |Cite
|
Sign up to set email alerts
|

Performance Study of BCH Error Correcting Codes Using the Bit Error Rate Term BER

Abstract: The quality of a digital transmission is mainly dependent on the amount of errors introduced into the transmission channel. The codes BCH (Bose-Chaudhuri-Hocquenghem) are widely used in communication systems and storage systems. In this paper a Performance study of BCH error correcting codes is proposed. This paper presents a comparative study of performance between the Bose-Chaudhuri-Hocquenghem codes BCH (15, 7, 2) and BCH (255, 231, 3) using the bit error rate term (BER). The channel and the modulation type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…From this figure we deduce that the BER performances of PHR-BM far exceed the HSDec and DND decoders. In the Figure 7.we present a comparison between HSDec [22], ARDecGA [21], BERT [6] and the proposed combination PHR-BM for the BCH (15,7,5) code. From this figure, we can deduce that our decoder PHR-BM passes remarkably the HSDec, ARDecGA and BERT decoders for this code.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this figure we deduce that the BER performances of PHR-BM far exceed the HSDec and DND decoders. In the Figure 7.we present a comparison between HSDec [22], ARDecGA [21], BERT [6] and the proposed combination PHR-BM for the BCH (15,7,5) code. From this figure, we can deduce that our decoder PHR-BM passes remarkably the HSDec, ARDecGA and BERT decoders for this code.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…They are just applicable for Quadratic Residue (QR) codes. By exploiting the Bit Error Rate Term, El ghayyaty et al [6] have published a performances study of BCH error correcting codes and they gave a comparative study between the BCH (15,7,2) and BCH(255, 231, 3) codes. In [7], quadratic residue codes were discussed over a defined ring.…”
Section: Relatedworkmentioning
confidence: 99%
“…To show the efficiency of our decoding model, we have compared its performances with other existing decoders. In Figure 11, we present the performances of the LRDec, ARDecGA [11] and BERT [12] decoders for the BCH code (15,7,5). Thanks to the comparisons listed above, the LRDec for the code BCH (15, 7, 5) has proved to be the best decoder in terms of performance and efficiency.…”
Section: Comparison and Discussionmentioning
confidence: 99%
“…For the same purpose, as shown in Figure 12, the LRDec and the HSDec [9] have the same performance in the code BCH (31, 16, 7). What is more, in Figure 13, we have compared the performance of LRDec with HSDec for a new class of binary code, the QR code (23,12,7), and the results have shown that the RLDec is more efficient than HSDec.…”
Section: Comparison and Discussionmentioning
confidence: 99%
See 1 more Smart Citation